Decomposition of Nitrous Oxide over Cu/TiO2 Catalysts: The Effect of Cu Loading, TiO2 Structure, and Reaction Conditions - K. Yanagida; W. Kurniawan; C. Salim; H. Hinode (Faculty of Engineering and Technology, Sampoerna University, 2019)
Decomposition of nitrous oxide (N2O) over titania (TiO2) supported copper (Cu) catalyst was investigated with the existence of oxygen and water vapor. The catalytic activity of TiO2 was promoted by copper loading. It was found that there are optimum levels of copper loading on TiO2, and these values are correlated to the specific surface area of TiO2 support being used. The relationship between the catalytic activity for decomposition of N2O and the crystal structure of TiO2 was also investigated. The result revealed that Cu/TiO2 catalysts with the rutile structure has a higher activity toward N2O decomposition than those with the anatase structure. In this research, Cu(5wt%)/TiO2 prepared from TiO2 JRC-TIO-4 (reference catalyst provided by Catalysis Society of Japan) which was mainly constituted of rutile showed the highest activity for N2O decomposition and it could decompose N2O completely at 650℃. The catalytic activity was inhibited by the existence of oxygen. However, there was no influence of water vapor to the catalytic activity of Cu/TiO2 for N2O decomposition.